2022
DOI: 10.1038/s41598-022-22223-y
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning approach to explore predictors of graft detachment following posterior lamellar keratoplasty: a nationwide registry study

Abstract: Machine learning can be used to explore the complex multifactorial patterns underlying postsurgical graft detachment after endothelial corneal transplantation surgery and to evaluate the marginal effect of various practice pattern modulations. We included all posterior lamellar keratoplasty procedures recorded in the Dutch Cornea Transplant Registry from 2015 through 2018 and collected the center-specific practice patterns using a questionnaire. All available data regarding the donor, recipient, surgery, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
2
8
0
1
Order By: Relevance
“…It has been reported that patients with prior failed transplants are at higher risk of requiring regrafting with subsequent corneal transplants. 12 , 13 Although not statistically significant, our findings are in line with this finding; patients for whom a regraft was necessary were more likely to have already had a history of prior transplant when compared to those patients who did not need a regraft (50% versus 36.9%, respectively; p = 0.264). Time in preservation and DTC seemed to be most related to the need to regraft, though neither achieved statistical significance.…”
Section: Resultssupporting
confidence: 83%
“…It has been reported that patients with prior failed transplants are at higher risk of requiring regrafting with subsequent corneal transplants. 12 , 13 Although not statistically significant, our findings are in line with this finding; patients for whom a regraft was necessary were more likely to have already had a history of prior transplant when compared to those patients who did not need a regraft (50% versus 36.9%, respectively; p = 0.264). Time in preservation and DTC seemed to be most related to the need to regraft, though neither achieved statistical significance.…”
Section: Resultssupporting
confidence: 83%
“…These differences will, however, be recorded during the data entry on the day of surgery into the eCRF. We standardise using an air tamponade because gas is, according to a data registry from the Netherlands, associated with poorer outcomes 24…”
Section: Methods and Analysismentioning
confidence: 99%
“…Overall, a growing body of evidence supports the use of AI-based pre- and postoperative screening as a tool that could help with predicting and diagnosing pathologic consequences of surgery. 14 , 19 , 30 , 32 , 33 Deep learning models have been employed to identify postoperative DMEK graft detachments, 19 to predict future need and suitability for keratoplasty, 30 to quantify DMEK graft detachment segmentation, 32 to identify the best predictors for graft detachment after endothelial keratoplasty, 33 and to predict the need for rebubbling after DMEK surgery. 34 Indeed, clinical trials are currently starting to incorporate AI into corneal pathology identification.…”
Section: Discussionmentioning
confidence: 99%